Winter precipitation over the Iberian peninsula and its relationship to circulation indices - C. Rodríguez-Puebla; A. H. Encinas; J. Sáenz (Copernicus Publications, 2001)
Winter precipitation variability over the Iberian peninsula was investigated by obtaining the spatial and temporal patterns. Empirical Orthogonal Functions were used to describe the variance distribution and to compress the precipitation data into a few modes. The corresponding spatial patterns divide the peninsula into climatic regions according to precipitation variations. The associated time series were related to large scale circulation indices and tropical sea surface temperature anomalies by using lag cross-correlation and cross-spectrum. The major findings are: the most influential indices for winter precipitation were the North Atlantic Oscillation and the East Atlantic/West Russian pattern; coherent oscillations were detected at about eight years between precipitation and the North Atlantic Oscillation and some dynamic consequences of the circulation on precipitation over the Iberian peninsula were examined during drought and wet spells. In the end statistical methods have been proposed to downscale seasonal precipitation prediction. Keywords: Winter precipitation, circulation indices, Iberian peninsula climate, climate variations, precipitation trend